2018
DOI: 10.1136/thoraxjnl-2017-211466
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of transcutaneous carbon dioxide monitoring: a systematic review and meta-analysis

Abstract: PROSPERO; CRD42017057450.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 24 publications
2
57
0
2
Order By: Relevance
“…To conclude this chapter, and in accordance with abundant concordant literature, we advocate the potential use of TCM in ICUs for ventilator management, because of its non-invasiveness, continuous monitoring, and accuracy of the transcutaneous CO 2 sensor technology (2,5,13,15,22,(24)(25)(26). For the longitudinal use as a trending monitor, we support the application of iterative punctual invasive artPCO 2 measurements with blood gas analysis to recalibrate and rescale the difference between arterial and transcutaneous PCO 2 value, or tc-art ΔPCO 2 gap (13,22). In this way, TCM could perform an interesting sniffing function over time to track artPCO2 elevation during therapeutic procedures such as prolonged NIV.…”
Section: Summary Of the Clinical Evidence For Tcpco 2 As A Reliable Amentioning
confidence: 64%
See 1 more Smart Citation
“…To conclude this chapter, and in accordance with abundant concordant literature, we advocate the potential use of TCM in ICUs for ventilator management, because of its non-invasiveness, continuous monitoring, and accuracy of the transcutaneous CO 2 sensor technology (2,5,13,15,22,(24)(25)(26). For the longitudinal use as a trending monitor, we support the application of iterative punctual invasive artPCO 2 measurements with blood gas analysis to recalibrate and rescale the difference between arterial and transcutaneous PCO 2 value, or tc-art ΔPCO 2 gap (13,22). In this way, TCM could perform an interesting sniffing function over time to track artPCO2 elevation during therapeutic procedures such as prolonged NIV.…”
Section: Summary Of the Clinical Evidence For Tcpco 2 As A Reliable Amentioning
confidence: 64%
“…In the whole population, they concluded that there are substantial differences between tcPCO 2 and artPCO 2 depending on the technical aspects (17,20,21), such as location site or temperature of electrode, and advocated the ear lobe as the site and a heated electrode of more than 42 ℃ for the temperature. However, these authors stated that the available literature attests to TCM being an accurate tool to estimate artPCO 2 to a clinically acceptable degree in the adult ICU population (22).…”
Section: Summary Of the Clinical Evidence For Tcpco 2 As A Reliable Amentioning
confidence: 99%
“…49,50 Similarly, transcutaneous arterial CO 2 measurements have shown mixed results and cannot replace arterial blood gas analysis. [51][52][53][54] Advanced Monitoring for Patients on Oxygen Therapy…”
Section: Arterial Blood Gas Analysismentioning
confidence: 99%
“…A recent systematic review and meta-analysis estimated pooled mean bias and population limits of agreement (LoA) between PtcCO2 and PaCO2. 253 Data from 73 studies published between 2000 and 2016 were analysed and included 7021 paired measurements taken from 2817 participants. For the analysis, an outer confidence bounds for 95% LoA of 1kPa between PtcCO2 and PaCO2 was deemed as clinically acceptable.…”
Section: Accuracy Of Transcutaneous Co2mentioning
confidence: 99%